2003
DOI: 10.1002/cncr.11817
|View full text |Cite
|
Sign up to set email alerts
|

Improved prevention of moderately emetogenic chemotherapy‐induced nausea and vomiting with palonosetron, a pharmacologically novel 5‐HT3 receptor antagonist

Abstract: BACKGROUNDPalonosetron, a highly selective and potent 5‐HT3 receptor antagonist with a strong binding affinity and a long plasma elimination half‐life (approximately 40 hours), has shown efficacy in Phase II trials in preventing chemotherapy‐induced nausea and vomiting (CINV) resulting from highly emetogenic chemotherapy. The current Phase III trial evaluated the efficacy and safety of palonosetron in preventing acute and delayed CINV after moderately emetogenic chemotherapy.METHODSIn the current study, 592 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
306
4
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(324 citation statements)
references
References 12 publications
8
306
4
4
Order By: Relevance
“…With respect to electrocardiogram abnormalities, it is important to note that in contrast to historical studies in adult cancer patients, the incidence of prolonged QT interval was low in the ondansetron group in this study (two [1%] of 164 patients). 13,14 Similarly, the incidence in the palonosetron groups was low, with this event reported for only one (<1%) of 163 patients in the 20 µg/kg group. Throughout the entire study, no study drug related treatment-emergent adverse events with a fatal outcome were recorded, and no patients discontinued the study due to drug-related treatment-emergent adverse events.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…With respect to electrocardiogram abnormalities, it is important to note that in contrast to historical studies in adult cancer patients, the incidence of prolonged QT interval was low in the ondansetron group in this study (two [1%] of 164 patients). 13,14 Similarly, the incidence in the palonosetron groups was low, with this event reported for only one (<1%) of 163 patients in the 20 µg/kg group. Throughout the entire study, no study drug related treatment-emergent adverse events with a fatal outcome were recorded, and no patients discontinued the study due to drug-related treatment-emergent adverse events.…”
Section: Discussionmentioning
confidence: 94%
“…[13][14][15] _ENREF_12 Palonosetron has also been shown to have greater receptor selectivity, longer duration of action, and unique structural characteristics compared with other 5-HT 3 receptor antagonists. 13,[16][17][18][19][20] Palonosetron also appears to have an advantageous safety profile compared with ondansetron, granisetron, dolasetron, and tropisetron, which have been associated with electrocardiographic changes and arrhythmias, sometimes leading to the potentially fatal heart rhythm torsades de pointes. 13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,11,76 Some studies have indicated that palonosetron is superior to first-generation 5-HT 3 receptor antagonists (ondansetron and dolasetron), but only for secondary end points (prevention of delayed emesis and overall tolerability) because primary end points were met (no vomiting and no rescue medication required) in all studies. 8,76,77 The more important issue is not the possible superiority of palonosetron to older 5-HT 3 receptor antagonists, but rather whether palonosetron is better than earlier 5-HT 3 receptor antagonists when combined with other drugs (specifically dexamethasone, a corticosteroid, and aprepitant). 76 There have been no prospective trials designed specifically to prove the superiority of palonosetron over any 5-HT 3 receptor antagonist and no prospective trials comparing palonosetron with another 5-HT 3 receptor antagonist when both are combined with dexamethasone.…”
Section: Pharmaceuticalmentioning
confidence: 99%
“…4 In the 1990s, the introduction of serotonin receptor antagonists (5-HT 3 RAs) improved the management of acute CINV associated with both moderately and highly emetogenic CT, [5][6][7][8] but no improvement was shown in the prophylaxis of delayed CINV. [9][10][11][12] The second-generation 5-HT 3 RA, namely palonosetron, and the neurokinin receptor antagonist, aprepitant, have improved not only the prevention of acute CINV, but also the prophylaxis of delayed CINV [13][14][15][16][17][18][19] after both moderately and highly emetogenic CT. However, control of delayed CINV is still an open problem, especially in patients undergoing multiple-day [20][21][22][23] or high-dose (HD)-CT. [24][25][26][27] Two recent studies 28,29 have shown the efficacy and safety of palonosetron plus dexamethasone in preventing CINV during and after multiple-day CT.…”
Section: Introductionmentioning
confidence: 99%